"Shopper, Buyer, and Consumer Behavior: Theory, Marketing Applications, and Public Policy Implications" - Lindquist (Jay D); Sirgy (Joseph M) ("19A, Ansari Road,New Delhi-110 002", 2005)
Consumer Behavior ; Sales
22.5
Keywords: Consumer Behavior ; Sales